Forensic ancestry analysis with two capillary electrophoresis ancestry informative marker (AIM) panels: Results of a collaborative EDNAP exercise. (November 2015) - Santos, C.; Fondevila, M.; Ballard, D.; Banemann, R.; Bento, A.M.; Børsting, C.; Branicki, W.; Brisighelli, F.; Burrington, M.; Capal, T.; Chaitanya, L.; Daniel, R.; et al.
Graphical abstract: Highlights: Nineteen laboratories completed a collaborative EDNAP exercise to evaluate two forensic ancestry informative marker (AIM) assays and accompanying statistical tools to infer ancestry from the genotype data. Laboratories were sent primers, reference data and five test DNAs of undisclosed origin plus an unmarked DNA mixture (but reported to be one of the samples). Fourteen laboratories successfully genotyped the DNAs with a 34-plex SNP assay using SNaPshot, achieving 96.1% profile completeness and 93.5% genotype concordance. All laboratories successfully genotyped the DNAs with a 46-plex Indel assay using dye-labelled PCR primers, achieving 99.8% profile completeness and genotype concordance. All laboratories identified the mixed DNA sample, indicated by disrupted peak height ratios in the Indel profile and three-allele patterns in SNP rs5030240. 18/19 laboratories assigned the correct ancestry to each of the test DNAs of unknown origin, obtaining likelihood ratios from 80 markers in the range: 1.25E + 07 to 1.78E + 41. Abstract: There is increasing interest in forensic ancestry tests, which are part of a growing number of DNA analyses that can enhance routine profiling by obtaining additional genetic information about unidentified DNA donors. Nearly all ancestry tests use single nucleotide polymorphisms (SNPs), but these currently rely on SNaPshot single base extension chemistry that can fail to detect mixed DNA. Insertion-deletion polymorphism (Indel) tests have been developed using dye-labeled primers that allow direct capillary electrophoresis detection of PCR products (PCR-to-CE). PCR-to-CE maintains the direct relationship between input DNA and signal strength as each marker is detected with a single dye, so mixed DNA is more reliably detected. We report the results of a collaborative inter-laboratory exercise of 19 participants (15 from the EDNAP European DNA Profiling group) that assessed a 34-plex SNP test using SNaPshot and a 46-plex Indel test using PCR-to-CE. Laboratories were asked to type five samples with different ancestries and detect an additional mixed DNA sample. Statistical inference of ancestry was made by participants using the Snipper online Bayes analysis portal plus an optional PCA module that analyzes the genotype data alongside calculation of Bayes likelihood ratios. Exercise results indicated consistent genotyping performance from both tests, reaching a particularly high level of reliability for the Indel test. SNP genotyping gave 93.5% concordance (compared to the organizing laboratory's data) that rose to 97.3% excluding one laboratory with a large number of miscalled genotypes. Indel genotyping gave a higher concordance rate of 99.8% and a reduced no-call rate compared to SNP analysis. All participants detected the mixture from their Indel peak height data and successfully assigned the correct ancestry to the other samples using Snippe r, with the exception of one laboratory with SNP miscalls that incorrectly assigned ancestry of two samples and did not obtain informative likelihood ratios for a third. Therefore, successful ancestry assignments were achieved by participants in 92 of 95 Snipper analyses. This exercise demonstrates that ancestry inference tests based on binary marker sets can be readily adopted by laboratories that already have well-established CE regimes in place. The Indel test proved to be easy to use and allowed all exercise participants to detect the DNA mixture as well as achieving complete and concordant profiles in nearly all cases. Lastly, two participants successfully ran parallel next-generation sequencing analyses (each using different systems) and achieved high levels of genotyping concordance using the exercise PCR primer mixes unmodified.